Communities catalyzing change with data to mitigate an invisible menace, traffic-related air pollution - Linda Sprague Martinez; Shir Lerman Ginzburg; Sharon Ron; Cristina Araujo Brinkerhoff; Samiya Haque; Sophia Angali England; Kynza Khimani; Wig Zamore; Ellin Reisner; Lydia Lowe; Doug Brugge (BMC, 2024)
Abstract Objectives To identify strategies and tactics communities use to translate research into environmental health action. Methods We employed a qualitative case study design to explore public health action conducted by residents, organizers, and public health planners in two Massachusetts communities as part of a community based participatory (CBPR) research study. Data sources included key informant interviews (n = 24), reports and direct observation of research and community meetings (n = 10) and project meeting minutes from 2016-2021. Data were coded deductively drawing on the community organizing and implementation frameworks. Results In Boston Chinatown, partners drew broad participation from community-based organizations, residents, and municipal leaders, which resulted in air pollution mitigation efforts being embedded in the master planning process. In Somerville, partners focused on change at multiple levels, developer behavior, and separate from the funded research, local legislative efforts, and litigation. Conclusions CBPR affords communities the ability to environmental health efforts in a way that is locally meaningful, leveraging their respective strengths. External facilitation can support the continuity and sustainment of community led CBPR efforts.